UJI TINGKAT KESADARAN KEAMANAN INFORMASI PENGGUNA SMARTPHONE (STUDI KASUS: AMIK LABUHAN BATU) - Ibnu Rasyid Munthe; Iwan Purnama (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2019)
Based on statistical data, it is known that Android is the most popular smartphone with the largest number of users in the world, which is around 1.8 billion users. The high number of users also invites many cases of information security and privacy caused by a lack of awareness from users such as spam, spoofing / phishing, network incidents, malware, uploading something of a personal nature such as photos, telephone numbers, addresses or not having antivirus. This study aims to find out about information security and privacy of Android smartphone users by measuring the problem of the dimension of awareness (attitude, knowledge and behavior) with seven focus areas of information security namely trust in app repositories, misconception about app testing, security and agreement messages, pirated application, adoption of security control, spam sms and report of security incidents and three focus areas on privacy namely perceived surveillance, perceived intrusion, secondary use of information. This research uses analytical hierarchy process (AHP) method to measure the level of information security awareness and privacy of smartphone users. Overall, the results of the study indicate that information security has an average level of awareness (71%). But in the focus area the report for security incidents has a poor level of awareness (37%) this is because users prefer to solve their own information security problems experienced and privacy has an average level of awareness (76%). While the secondary use of information in the attitude dimension has a low level of awareness (66%). Based on these findings, it can be concluded that smartphone users at AMIK Labuhan Batu have a poor level of awareness in maintaining information security and privacy..